The role of the SA Advertising Research Founda- tion in communications research - Casper Venter (Communicare)
The South African Advertising Research Foundation started operations in January 1975. The SAARF is financed by a levy of 0.5 per cent added by the media to their published advertising rates. The primary objectives of the SAARF are to develop an organisation for research which can conduct, promote, and sponsor comprehensive and continuous audience and product usage surveys. It further aims to improve professional standards and methods of research as well as the effective use of research results; to sponsor relevant education and research by tertiary education institutions; and to liaise with international organisations involved in advertising and marketing research. Up to now six All media and product surveys have been conducted. The cost per interview in AMPS studies compare very favourably with costs overseas It is concluded that total involvement of all concerned, including academic institutions, is essential for raising the research standards even more